GLADE+ : an extended galaxy catalogue for multimessenger searches with advanced gravitational-wave detectors. Issue 1 (30th May 2022) - Dálya, G; Díaz, R; Bouchet, F R; Frei, Z; Jasche, J; Lavaux, G; Macas, R; Mukherjee, S; Pálfi, M; de Souza, R S; Wandelt, B D; Bilicki, M; et al.
ABSTRACT: We present GLADE+, an extended version of the GLADE galaxy catalogue introduced in our previous paper for multimessenger searches with advanced gravitational-wave detectors. GLADE+ combines data from six separate but not independent astronomical catalogues: the GWGC, 2MPZ, 2MASS XSC, HyperLEDA, and WISExSCOSPZ galaxy catalogues, and the SDSS-DR16Q quasar catalogue. To allow corrections of CMB-frame redshifts for peculiar motions, we calculated peculiar velocities along with their standard deviations of all galaxies having B -band magnitude data within redshift z  = 0.05 using the 'Bayesian Origin Reconstruction from Galaxies' formalism. GLADE+ is complete up to luminosity distance $d_L=47^{+4}_{-2}$ Mpc in terms of the total expected B -band luminosity of galaxies, and contains all of the brightest galaxies giving 90 per cent of the total B -band and K -band luminosity up to dL ≃ 130 Mpc. We include estimations of stellar masses and individual binary neutron star merger rates for galaxies with W 1 magnitudes. These parameters can help in ranking galaxies in a given gravitational wave localization volume in terms of their likelihood of being hosts, thereby possibly reducing the number of pointings and total integration time needed to find the electromagnetic counterpart.